Students' Learning Styles Based on Multiple Intelligences Theory in Solid Geometry Learning : A Phenomenological Study Of 8th Grade Junior High School - Dzakiyah 'Izzah Ghassani Adsumi; Siti Nuraini; Toto Subroto; Sri Asnawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This study aims to explore how eighth-grade students’ learning styles, based on Multiple Intelligences, manifest in geometry learning, and to address the research question: How can learning diversity in solving geometry tasks be revealed through the lens of the eight Multiple Intelligences? Using a qualitative approach with a descriptive phenomenological method, nine participants (N = 9) were purposively selected from a pool of 357 students through questionnaires, interviews, observations, and artifact analysis. Each participant represented one of six dominant intelligences according to the theories of Gardner and Armstrong (2018). The findings show that instruction tailored to students’ dominant intelligences enabled them to complete tasks in distinctive ways—for example, building physical models for kinesthetic learners or composing mathematical narratives for verbal learners. This adaptation facilitated active engagement, deeper conceptual understanding, and authentic learning expression. The study highlights the importance of intelligence-based differentiated instruction in geometry teaching to optimize diverse learning potentials.